Kotekan Technique As An Idea For The Creative Process In Music Creation - Ardiansyah, Aris; Mohamad Rudiana; Sukmawati Saleh (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
The creative process in the creation of musical works is a multifaceted journey that begins with the acquisition of ideas or inspirations. These ideas are transformed into musical concepts, which are then meticulously developed into compositions that are played using a variety of instruments, each representing the unique vision of the creator or composer. This transformation reaches its conclusion in the realisation of the compositions in the form of live performances, which may be experienced as both audio-visual experiences and music recordings. It is also noteworthy that this creative process has the additional function of serving educational purposes. Such activities have the potential to encourage collective action and community engagement, thereby strengthening social solidarity among participants. This research employs an interpretative qualitative methodology, drawing upon literature studies, audio-visual sources, and the empirical experiences of the researcher as both a musician and educator in the field of music. This interpretative approach entails a meticulous examination of selected and organized data through the triangulation of multiple sources. The interpretative phase is enhanced by a synthesis of creative processes and theoretical frameworks, thereby facilitating a comprehensive understanding of the complex relationship between musical creation and its cultural implications. This study illuminates the significance of the creative process in both individual and communal contexts, demonstrating its capacity to shape musical identity and foster social connections.